Study on the impact of rural public sports facilities and instructors on residents’ participation in sports activities in China - Xiujin Guo; Xiangjun Yang; Sujie Mao (Frontiers in Public Health)
ObjectiveThis study aims to explore how rural public sports facilities and their instructors influence the participation of rural residents in sports activities under the background of China’s rural revitalization strategy. The goal is to provide strategies for the effective use and management of rural sports facilities, thereby encouraging rural residents to actively participate in sports activities, improve their quality of life, and support comprehensive rural revitalization.MethodsA cross-sectional study design was used, employing a stratified sampling method to distribute questionnaires to 5,000 residents in the eastern, central, western, and southern regions of China. Data analysis was conducted using R4.1.3 software. The main research indicators included the funding sources of sports facilities and the composition of social sports instructors, while residents’ basic characteristics were considered secondary indicators for correlation, regression, and cross-analysis.ResultsAnalysis of 3,956 valid questionnaires revealed that increasing age led to a decrease in the frequency of sports activities (−0.098), while higher education levels increased activity frequency (0.097). Facilities provided by county sports bureaus significantly promoted participation in sports activities (B = 0.320, p < 0.001). Facilities donated by villagers or township enterprises and the sports lottery fund also effectively increased participation (B = 0.219, p < 0.001; B = 0.159, p = 0.011). Sports facility instructors, particularly urban residents and retirees, significantly positively impacted activity time, while the absence of instructors reduced residents’ participation in sports activities (B = −0.445, p < 0.001).ConclusionAge and education level are negatively correlated with sports activity participation, while the source of public sports facilities, especially those provided by county sports bureaus, the sports lottery fund, and village committees, significantly enhance participation. The presence of social sports instructors significantly increases the time and frequency of residents’ sports activities. Policymakers need to focus on the construction and management of public sports facilities, develop and utilize diversified funding sources, and enhance the role of sports facility instructors. By providing professional guidance and organizing diverse sports activities, rural residents’ enthusiasm for participation can be effectively stimulated.